Answer:
Jane is 12 and Harvey is 36
Step-by-step explanation:
Hello there!
3x - y = 3
-x + y = 3
We need to solve 3x - y = 3 for y
Let start by adding -3x to both sides
3x - y = 3
3x - 3x - y = 3 - 3x
-y = 3 - 3x
We cannot leave the variable with a negative sign. We must multiply both sides by -1
-y * -1= (3 - 3x)-1
y = 3x - 3
Substitute 3x -3 for y in -x+y=3
-x + y = 3
-x + 3x - 3 = 3
2x - 3 = 3
2x = 3 + 3
2x = 6
x = 6/2
x = 3
Now substitute 3 for x in y=3x -3
y = 3x - 3
y = 3(3) - 3
y= 9 - 3
y= 6
Thus,
The answer is x=3 and y=6
It is always my pleasure to help students like you :)
As always, I am here to help!
Answer:
2×(1+10)
Step-by-Step
You are just substituting in where the parenthesis go.
But I am not entirely sure.
Answer:
<em>Good L</em>uck!
Step-by-step explanation: